Kvantiteter og kvaliteter i ungdomskriminaliteten - Britta Kyvsgaard (Nordisk Tidsskrift for Kriminalvidenskab)
From the beginning of the 1980's a decline in youth crime has been demonstrated by studies of self-reported delinquency as well as in the number of officially reported crime. At the same time an increase in crime among adults has taken place. In spite of this, youth crime attracts growing concern both generally and politically. In the article, the decrease in youth crime and the increase in concern is seen as having the same background: A growing intolerance towards crime. An increased socioeconomic marginalization among offenders can furthermore be seen as both resulting in and stimulating intolerance. Focus upon crime committed by immigrants and children of immigrants and a perceived growing brutalization in the youth crime might work in the same direction. Whether youth crime actually forms a greater threat to society today is still an unanswered question.